Molecular polymorphism in seedlings of Cattleya forbesii resulting from in vitro germination - Kuhn, Betty Cristiane; Claudino, Leticia Oliveira; Gutierre, Maria Auxiliadora Milanese; Mangolin, Claudete Aparecida; Machado, Maria de Fátima Pires da Silva (Acta Iguazu, 2018)
The aim of this study was to evaluate molecular polymorphism of in vitro samples of propagated Cattleya forbesii which are used to replace stocks and cultivation in nature. Molecular diversity in micro-propagated orchids has not been investigated. The genetic diversity of this species was studied using touchdown PCR (Polymerase Chain Reaction) for random amplified polymorphism DNA markers (td-PCR-RAPD). The 12 RAPD primers used in the present study generated 148 reproducible DNA segments, of which 132 were polymorphic. There were 89.19% polymorphism, and the number of bands for each primer varied from 7 to 17, with an average of 12.33 bands per primer. The large natural genetic variability previously described in studies examining populations distributed in their natural habitats was also observed in C. forbesii seedlings grown in vitro. The polymorphism of td-PCR-RAPD markers in C. forbesii seedlings from self-pollination and in vitro germination was high, indicating that the genetic diversity in this species does not suffer from the negative effects of self-pollination or in vitro propagation. In vitro culture of C. forbesii seeds was considered suitable to produce seedlings for replacing stocks, for cultivation in nature and to stimulate the production of hybrids.